2014
DOI: 10.2478/intox-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Ozone decomposition

Abstract: Catalytic ozone decomposition is of great significance because ozone is a toxic substance commonly found or generated in human environments (aircraft cabins, offices with photocopiers, laser printers, sterilizers). Considerable work has been done on ozone decomposition reported in the literature. This review provides a comprehensive summary of the literature, concentrating on analysis of the physico-chemical properties, synthesis and catalytic decomposition of ozone. This is supplemented by a review on kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 57 publications
3
99
0
Order By: Relevance
“…[11][12][13] A series of essential catalysts for ozone decomposition have been developed, of which the most active and productive candidates for catalytically converting ozone to oxygen molecules are indeed noble metals and transition metal oxides. 12,14 Transition metal oxide-based catalysts are incredibly efficient from an environmental perspective and simultaneously provide a convenient and affordable way to decompose the ozone molecules. In this regard, transition metal oxides including MnO 2 , [15][16][17] Cu 2 O/CuO, 10,18 Fe 2 O 3 , 19,20 and NiO 21 have been reported as active catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] A series of essential catalysts for ozone decomposition have been developed, of which the most active and productive candidates for catalytically converting ozone to oxygen molecules are indeed noble metals and transition metal oxides. 12,14 Transition metal oxide-based catalysts are incredibly efficient from an environmental perspective and simultaneously provide a convenient and affordable way to decompose the ozone molecules. In this regard, transition metal oxides including MnO 2 , [15][16][17] Cu 2 O/CuO, 10,18 Fe 2 O 3 , 19,20 and NiO 21 have been reported as active catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Note that gas-phase species, including O 3 , were not removed before introducing aerosols to the heating region, which could lead to artifacts via oxidation at high temperature. 44 We also 16…”
Section: Thermal Stability Of Soa Molecular Productsmentioning
confidence: 88%
“…Thus, Fe reacts with ozone faster than Cu, leading to ozone decomposition. Batakliev et al [2] investigated catalysts based on metals and their oxides in different oxidation levels and found that the catalytic activity of these metal oxides was increased by increasing the metal oxidation state. The catalytic activity degree of a number of elements to the decomposition of ozone was in the order Cu < Ag < Ni < Fe < Au < Pt.…”
Section: Catalytic Performances Of Parent and Transition Metals-loadementioning
confidence: 99%
“…On the other hand, the transition metals and their oxides have been found to be the most active substances for ozone decomposition [2]. Zeolite is characterized by its ability to participate in ion-exchange reactions [10].…”
mentioning
confidence: 99%